Framing by the Flock: Collective Issue Definition and Advocacy Success. (March 2019) - Junk, Wiebke Marie; Rasmussen, Anne
The framing of issues is part of the tool kit used by lobbyists in modern policy making, yet the ways in which framing works to affect lobbying success across issues remain underexplored. Analyzing a new dataset of lobbying in the news on 50 policy issues in five European countries, we demonstrate that it is not individual but collective framing that matters: Emphasis frames that enjoy collective backing from lobbying camps of like-minded advocates affect an advocate's success, rather than frames being voiced by individual advocates. Crucially, it matters for advocacy success whether the advocate's camp frames its policy goals on an issue in unity with "one voice" and whether the actor's camp wins the contest of framing the issue vis-à-vis the opposing camp. Our results emphasize the need to consider the collective mechanisms behind the power of framing and have implications for future research on framing as an advocacy tool.